Pola Asuh, Stimulasi Psikososial, Dan Status Gizi Balita Di Kabupaten Kudus - Ani Rahidha Proboningrum; Ali Khomsan (JURNAL NUTRISIA, 2016)
Background: Parenting pattern is an important part which also determines nutritional status of children. The effect of employed mother is less of parenting time so it can impact to the quality of parenting pattern provided to children. Objective:The purpose of this research was to study parenting pattern, psychosocial stimulation, and nutritional status among under-five children between employed mothers (as a cigarette factory workers) and not employed mother in Kudus district. Method :The research design was cross sectional study with 94 subjects of under-five children aged 3-5 years, divided into two groups are 38 subjects of employed mother and 56 subjects of not employed mother. Place of research was selected purposively in Jati and Mejobo subdistricts. Result : Mann Whitney test showed that there were significant difference of feeding practice and psychosocial stimulation between employed and not employed mothers. Rank Spearman test showed that there were relationship between mother’s education with feeding practice and psychosocial stimulation and also feeding practice with the nutritional status (WAZ and HAZ) (p <0.05). Conclusion: in General, the impact of the status of a mother who worked as a factory laborer smoking in this study i.e. decrease in allocation of time nurturing mother thus causing less good quality parenting meal given to balitanya as well as the low score psychosocial stimulation obtained during the toddler in the House. Keywords: employed and not employed mother, nutritional status, parenting pattern, psychosocial stimulation